Dominant and Absent Types of Application of Information Technology in Medical Education and its Challenges - Morteza Karami; Somayeh Ebrahimi Kooshk Mahdi (Kerman University of Medical Sciences, 2013)
Background & Objective: The aim of this article was to explore the use of new information and communication technology (ICT) in medical education in Mashhad University of Medical Sciences as a single case study Methods : The research method was descriptive The study population consisted of students and faculty member of Mashhad University of Medical Sciences Iran Stratified sampling was used to investigate information technology in academic environments To investigate the ideal situation a random sampling method was applied Questionnaires observation survey and other methods were used to study ICT in higher education Results : There was a significant difference significantly higher than the mean between ICT use and the ideal condition in some cases and lower than the mean in others (P < 001) In some cases the difference was not significant which showed the moderate use of ICT The use of ICT is mainly in areas such as Word However its other possibilities like communication are not used Both groups had a positive attitude toward ICT and assessed their skills as moderate (P < 001) Conclusion : Results indicated a significant positive relationship between these three variables in both groups (P < 001) The ideal situation according to teachers and students included ICT training online library and improving infrastructure particularly internet speed They believed the main challenges to be their lack of skills educational policy and financial managerial cultural and infrastructural issues